2019
DOI: 10.1159/000493737
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Genital Disease in Men: What We Have Learned from the <b><i>HIM Study</i></b>

Abstract: It is currently recognized that in addition to the major impact of human papillomavirus (HPV) infection in females, HPV causes considerable disease in men at the genitals, anal canal, and oropharynx. Specifically, genital HPV infections may progress to genital warts and penile carcinoma. Although studies concerning the natural history of HPV infections and associated neoplasias have mainly focused on women, during the last 2 decades considerable attention has been given in further understanding these infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 72 publications
0
16
0
2
Order By: Relevance
“…HPV detection at a single time cannot represent persistent HPV infections. A prospective study found that 66% and 90% of HPV infections would be cleared within 12 and 24 months, respectively, in men [35]. Consecutive HPV testing will be conducted at the 12-month visit to further understand the natural history of HPV infections among MSM attending university.…”
Section: Discussionmentioning
confidence: 99%
“…HPV detection at a single time cannot represent persistent HPV infections. A prospective study found that 66% and 90% of HPV infections would be cleared within 12 and 24 months, respectively, in men [35]. Consecutive HPV testing will be conducted at the 12-month visit to further understand the natural history of HPV infections among MSM attending university.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Based on previous studies of mechanisms of transmission and the virus-related carcinogenesis, early diagnosis and treatment of a clinical HPV infection in men is potentially beneficial, once its eradication may reduce the viral reservoir and, as a consequence, reduce the incidence of cervical cancer and other HPV-related diseases. [21][22][23][24] Treatment should be targeted at the clinical manifestations of Despite the disease's high clearance rate, longitudinal studies including patients' partners evaluation based on several diagnostic tools are still needed to increment our knowledge on the disease behavior and its consequences, especially from the oncologic perspective in the mid-and long-term.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies of mechanisms of transmission and the virus‐related carcinogenesis, early diagnosis and treatment of a clinical HPV infection in men is potentially beneficial, once its eradication may reduce the viral reservoir and, as a consequence, reduce the incidence of cervical cancer and other HPV‐related diseases 21‐24 …”
Section: Discussionmentioning
confidence: 99%
“…There have been over 100 types of HPV identi ed with around 40 strains that are known to affect the anogenital area [3]. Though primarily (90%) HPV genotypes 6 and 11 are known to be associated with external anogenital warts, combined infections with other low-risk (LR) and high-risk (HR) HPV types also occur [4][5][6][7][8][9]. People who are between 18 to 59 years of age are most commonly affected, with the highest frequency reported of 20-35 years.…”
Section: Introductionmentioning
confidence: 99%